Protein quality control pathways at the crossroad of synucleinopathies - Mattos, Eduardo P. de; Wentink, Anne; Nussbaum-Krammer, Carmen; Hansen, Christian; Bergink, Steven; Melki, Ronald; Kampinga, Harm H. (Journal of Parkinson's Disease, 2020)
The pathophysiology of Parkinson's disease, dementia with Lewy bodies, multiple system atrophy, and many others converge at alpha-synuclein (alpha-Syn) aggregation. Although it is still not entirely clear what precise biophysical processes act as triggers, cumulative evidence points towards a crucial role for protein quality control (PQC) systems in modulating alpha-Syn aggregation and toxicity. These encompass distinct cellular strategies that tightly balance protein production, stability, and degradation, ultimately regulating alpha-Syn levels. Here, we review the main aspects of alpha-Syn biology, focusing on the cellular PQC components that are at the heart of recognizing and disposing toxic, aggregate-prone alpha-Syn assemblies: molecular chaperones and the ubiquitin-proteasome system and autophagy-lysosome pathway, respectively. A deeper understanding of these basic protein homeostasis mechanisms might contribute to the development of new therapeutic strategies envisioning the prevention and/or enhanced degradation of alpha-Syn aggregates.
Gesehen am 02.07.2020